Social impact bonds and public service reform: back to the future of New Public Management? - French, Max; Kimmitt, Jonathan; Wilson, Rob; Jamieson, David; Lowe, Toby (International public management journal, 2023)
This article explores where the increasing adoption of SIBs and outcomes-based contracting may lead public service systems-toward New Public Governance, or 'back' to New Public Management. We present analysis from the first significant longitudinal qualitative study of a major UK SIB focused on improving outcomes in the context of social determinants of health to analyze how the two governance logics manifest and interact across the SIB lifecourse. We find that while both governance logics were present at initiation, over time NPM elements strengthened while NPG elements weakened. Two inalienable elements of the SIB model-investor power and data requirements for contract management-appeared to drive this change. Our findings provide evidence that SIBs promote a retrenchment of NPM, rather than a transition to NPG or a hybridization of the two governance logics. Findings also show how NPM, rather than a transitional stage toward NPG, can prove the more resilient and dominant governance logic within institutional forms.